Bactericidal Activity of Lipid-Shelled Nitric Oxide-Loaded Microbubbles - Lafond, Maxime; Shekhar, Himanshu; Panmanee, Warunya; Collins, Sydney D.; Palaniappan, Arunkumar; McDaniel, Cameron T.; Hassett, Daniel J.; Holland, Christy K. (Frontiers in Pharmacology, 2020)
The global pandemic of antibiotic resistance is an ever-burgeoning public health challenge, motivating the development of adjunct bactericidal therapies. Nitric oxide (NO) is a potent bioactive gas that induces a variety of therapeutic effects, including bactericidal and biofilm dispersion properties. The short half-life, high reactivity, and rapid diffusivity of NO make therapeutic delivery challenging. The goal of this work was to characterize NO-loaded microbubbles stabilized with a lipid shell and to assess the feasibility of antibacterial therapy in vitro. Microbubbles (MB) were loaded with either NO alone (NO-MB) or with NO and octafluoropropane (NO-OFP-MB) (9:1 v/v and 1:1 v/v). The size distribution and acoustic attenuation coefficient of NO-MB and NO-OFP-MB were measured. Ultrasound-triggered release of the encapsulated gas payload was demonstrated with 3-MHz pulsed Doppler ultrasound. An amperometric micro-electrode sensor was used to measure NO concentration released from the microbubbles and compared to an NO-OFP-saturated solution. The effect of NO delivery on the viability of planktonic (free living) Staphylococcus aureus (SA) USA 300, a methicillin-resistant strain, was evaluated in a 96 well-plate format. The co-encapsulation of NO with OFP increased the total volume and attenuation coefficient of microbubbles. The NO-OFP-MB were destroyed with a clinical ultrasound scanner at an output with an MI of 1.2 but maintained their echogenicity at an MI of 0.04. The NO dose in NO-MB and NO-OFP-MB was more than 2-fold higher than the NO-OFP-saturated solution. Delivery of NO-OFP-MB increased bactericidal efficacy compared to the NO-OFP-saturated solution or air and OFP-loaded microbubbles. These results suggest that encapsulation of NO with OFP in lipid-shelled microbubbles enhances payload delivery. Furthermore, these studies demonstrate the feasibility and limitations of NO-OFP-MB for antibacterial applications.